Transforming Group Treatment in Acute Psychiatry: The CPA Model - Bornmann, Barbara A.; Jagatic, George (International Journal of Psychosocial Rehabilitation, 2018)
In acute psychiatry, regulatory guidelines require a shorter length of stay which demands greater organiz- ation of group treatment that serves a patient’s individual treatment goals. Kings County Hospital, in re- sponse to a federal mandate, developed the Central Program Area (“CPA”) group program to provide cat- egorized interdisciplinary group treatment that delivers a skill building approach to help patients in their recovery process. Through a commitment to person-centered care, the CPA, a person-centered group programming model was developed. Within the CPA model, group therapy approaches to curriculum such as the Road to Home, which provides group treatment for patients with substance abuse issues, are discussed. Efficacy measures on program implementation indicate that providing CPA group program- ming increased patient engagement in prescribed group treatment from 47% to 69%, and through the re- view of the Group Notes weekly group programming summary in treatment team meetings, staff report that patients practiced and reinforced new recovery skills.